Fishing Tourism as an Opportunity for Sustainable Rural Development—The Case of Galicia, Spain - Rubén C. Lois González; María de los Ángeles Piñeiro Antelo (Land, 2020)
The functional diversification of coastal fishing communities has been a central objective of the Common Fisheries Policy (CFP) since the early stages of its implementation. A large part of the initiatives financed throughout Europe have been linked to the creation of synergies between the fishing sector and tourism. This paper analyses the opportunities for the development of fishing tourism at the regional level, considering the investments of European and regional funds on the development of fishing tourism in Galicia. Special attention is given to the incorporation of the territorial perspective and Community-Led Local Development (CLLD) for the sustainable development of fishing areas. The results show limitations of this form of tourism in terms of employment and income, especially those developed by fishermen, despite the significant support of the regional government for this activity. This situation allows a critical reflection on the opportunity to convert fishermen into tourist guides, based on the need to diversify the economy and income of fishing communities.